2000
DOI: 10.1007/s004270000100
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death triggered by insect steroid hormone, 20-hydroxyecdysone, in the anterior silk gland of the silkworm, Bombyx mori

Abstract: Silk gland is a larval specific tissue of lepidopteran insects and begins to degenerate shortly before pupation. Programmed cell death (PCD) of the anterior silk gland of Bombyx mori last instar larvae was studied in vivo and in vitro, focusing on the effects of 20- hydroxyecdysone (20E). The glands began to exhibit signs of PCD in vivo 2 days after gut purge and completed PCD by 48 h. In vitro, 20E prematurely induced PCD, and its completion took 144 h (6 days). An oligo-nucleosomal ladder pattern was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 0 publications
5
100
0
Order By: Relevance
“…α-AMA does not show a direct cytolytic effect, but it does block DNA transcription by inhibiting the RPB1 subunit of RNA polymerase II, leading to cell death (15,16). Additionally, α-AMA induces both necrotic and apoptotic cell death concomitantly in the hepatocytes, where elevated cellular apoptosis is especially emphasized (2,18). In human fibroblasts and human colon carcinoma cell line 116 (HTC116), α-AMA was shown to induce the accumulation of p53 in the mitochondria, which leads to p53-and caspase-dependent apoptosis (16,21,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…α-AMA does not show a direct cytolytic effect, but it does block DNA transcription by inhibiting the RPB1 subunit of RNA polymerase II, leading to cell death (15,16). Additionally, α-AMA induces both necrotic and apoptotic cell death concomitantly in the hepatocytes, where elevated cellular apoptosis is especially emphasized (2,18). In human fibroblasts and human colon carcinoma cell line 116 (HTC116), α-AMA was shown to induce the accumulation of p53 in the mitochondria, which leads to p53-and caspase-dependent apoptosis (16,21,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments performed on canine hepatocyte cultures have shown that apoptosis plays a vital role in the pathogenesis of hepatic damage caused by α-AMA intoxication (2,18). The α-AMA-induced apoptosis is associated with severe liver damage, especially in the early stages of poisoning (18); however, a nonlethal dose of α-AMA prevents DD1 (a novel death domain)-mediated apoptosis by disrupting the protein synthesis. In fact, this process is under investigation in cell culture experiments either alone or in combination with other medicines for the treatment of cancer (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…170 In A. mellifera, cell autolytic activity is histochemically visualized in several regions 165 including the basal area of the epithelial cells in degenerating midgut. 166 Over the past several years apoptosis- [171][172][173][174] and autophagyrelated 51,53,142,144,174 pathways have been suggested to be involved in the degeneration of larval tissues and organs during metamorphosis in Lepidoptera. In these insects, as in the largest part of holometabolous insects, larvae and adults are characterized by diverse food and feeding habits.…”
Section: Pcd Of Nurse Cells and Follicle Cells Is Absolutely Requiredmentioning
confidence: 99%
“…ASGs were dissected on the day of gut purge (Terashima et al, 2000) and cultured separately in 0.3 ml Grace's insect culture medium (Gibco BRL, Rockville, MD) at 25°C for 18 h with 1 μM 20E, followed by culture in a hormone-free medium for further 12 h. Because the binding activity in membrane fractions prepared from cultured ASGs is higher than that in freshly dissected ASGs (Elmogy et al, 2004), we mainly used cultured ASGs.…”
Section: Animals and Asgsmentioning
confidence: 99%
“…The anterior silk glands (ASGs) of the silkworm, Bombyx mori, begin to undergo programmed cell death (PCD) in response to a high hemolymph concentration of ecdysteroid, which induces pupal metamorphosis (Terashima et al, 2000). The biologically active form of ecdysone, 20-hydroxyecdysone (20E), binds to a functional nuclear ecdysone receptor consisting of an ecdysone receptor (EcR) and its heterodimeric partner, Ultraspiracle (USP), and thereby controls the transcriptional activity of target genes (Riddiford et al, 2000).…”
Section: Introductionmentioning
confidence: 99%